2015
DOI: 10.1155/2015/616298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activities and Tyrosinase Inhibitory Property from Mycelium Culture Extracts

Abstract: Since mushrooms have many bioactive components, they have been used as components in folk medicine. Because mycelium has an advantage when it comes to large-scale production, this study aimed to evaluate the antioxidant properties and anti-tyrosinase activity from 55 mycelia in culture media. Relatively high 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging capacity was detected from the ethanol extract of culture media including mycelium (EECiM) of Morchella esculenta var. esculenta (MEVE), Auricularia polytric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Although Pleurotus species are the most studied mushroom species with reported anti-tyrosinase potential, none of those studies were able to identify the bioactive metabolites responsible for this activity. Park et al (2015b) recently studied the tyrosinase inhibitory activity of several ethanolic mycelium extracts in the presence of arbutin and ascorbic acid as positive controls. Among the studied extracts, Inonotus mikadoi (Lloyd) Gilb.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…Although Pleurotus species are the most studied mushroom species with reported anti-tyrosinase potential, none of those studies were able to identify the bioactive metabolites responsible for this activity. Park et al (2015b) recently studied the tyrosinase inhibitory activity of several ethanolic mycelium extracts in the presence of arbutin and ascorbic acid as positive controls. Among the studied extracts, Inonotus mikadoi (Lloyd) Gilb.…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…In these studies, both ethanol and water extracts of A. polytricha have significant antioxidant activities determined using different methods such as in vitro free radical scavenging assays, DPPH assay and TAS assay [29][30]. In a previously reported work, A. polytricha had high DPPH scavenging activity [31]. Another study showed that A. polytricha, which is among the edible mushrooms, had the strongest radical scavenging and metal chelating activities in addition to the highest polyphenolic and flavonoid contents [32].…”
Section: Determination Of Total Antioxidant Status (Tas) Of Extractsmentioning
confidence: 99%
“…Morchella spp (morel) is highly prized for its medicinal and nutritional qualities, such as antioxidant, anti-inflammatory and antitumor activities, as well as strengthening the immune response [1~4]. According to previous experiments, morel mycelia growth and fruit-body (ascocarp) formation are strongly affected by many factors, such as temperature, humidity, illumination, air, pH and nutrition.…”
Section: Introductionmentioning
confidence: 99%